Modeling of delay-insensitive circuit building blocks using the Hamburg Design System - Sacayanan, Jesse M. (Philippine Engineering Journal)
The operation of delay-insensitive circuits, a class of asynchronous logic circuits, is difficult to visualize. Models of delay insensitive circuit building blocks are created using the Hamburg Design System (HADES), a pure Java framework for object oriented component based simulation. These models help designers and students visualize the operation of delay insensitive circuits.